Sebuah Interpretasi ‘Refleksi’; Bayangan dan Makna Diri - Romli, Mohd Affwan Izam; Shaarani, Hamdan (Idealogy Journal; Vol 4 No 1 (2019): Idealogy Journal (April 2019), 2019)
Letter to Editor - No Abstract Abstrak Pandangan- tiada abstrak